HIV/AIDS and food crises: RENEWAL in Africa - Loevinsohn, Michael E.; Gillespie, Stuart (International Food Policy Research Institute, 2004)
"To effectively address the interactions between HIV/AIDS and food insecurity, there's a need to fill knowledge gaps. strengthen capacity, and learn-by-doing in partnership with people who are directly affected." -- from Text